Exploring the interconnectedness of multiple sclerosis and erectile dysfunction: mechanisms and management strategies - Zhang, Yongrui; Cao, Hongliang; Wang, Lei; Xu, Tao; Yuan, Bo (Frontiers in Cell and Developmental Biology, 2025)
Erectile dysfunction (ED) is common in men with multiple sclerosis (MS) and arises from convergent neurogenic, autonomic, vascular, inflammatory, and psychosocial pathways. We synthesize epidemiologic prevalence and risk data on ED in MS, map mechanistic pathways linking central and spinal lesions, autonomic–endothelial imbalance, and psychosocial modulators to ED phenotypes, and provide a stage-based care algorithm integrating neuro-urological testing and psycho-sexological support. Across more than 30 studies, pooled ED prevalence in men with MS is approximately 50%, with higher odds at greater disability and with co-existing lower urinary tract symptom (LUTS) and depression. Phosphodiesterase-5 inhibitors (PDE5i) are commonly used as first-line pharmacologic therapy, although data specific to MS remain limited and individual response can vary. Device-, injection-, neuromodulation-, and prosthesis-based options offer escalation pathways. Evidence quality varies and residual confounding and detection bias remain possible.